Greville Fane - James, Henry, 1843-1916 (Salt Lake City, UT : Project Gutenberg, 2001)
"Greville Fane" by Henry James is a novel written during the late 19th century. It explores the life and literary career of Mrs. Stormer, a fictional author, and the dynamics of her relationships with those around her, particularly her son Leolin and daughter Ethel. The book delves into themes of ambition, artistry, and the often shadowy intersection of personal lives and public personas in the world of literature. The narrative begins with the protagonist receiving a telegram about the death of Mrs. Stormer, prompting reflections on her life and literary contributions. Through a series of encounters and memories, the story unfolds the complexities of Mrs. Stormer's character$1 (Bher modest talents overshadowed by a vibrant social persona$1 (Band her ambitions for her children. Leolin embodies the youthful ambition and modernity that contrast with Greville's more traditional views on literature. The novel deftly critiques society's views on literary success, examining how Mrs. Stormer$1 (Bs lack of self-awareness and relentless optimism impacts her family, particularly as Leolin exploits her efforts for his own aspirations. The story culminates in a bittersweet acknowledgment of the inevitable decline of both Mrs. Stormer's literary fame and personal relevance in a changing world, ultimately leaving readers to ponder the cost of artistic ambition on familial bonds. (This is an automatically generated summary.)s
Release date is 2001-07-01
Transcribed from 1893 Macmillan and Co. edition by David Price. Proofed by Nina Hall, Mohua Sen, Bridie, Francine Smith and David
Keywords: Women authors -- Fiction